SEMANTIC ANALYSIS OF WHERE IS THE DIFFERENCE IN THE MEANING OF THE WORDS QALB AND FUĀD IN THE QUR'AN? - Andri; M Darojat Ariyanto; Muh Fuad Abror; Sayed Akhyar; Faisal bin Husen Ismail (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2023)
The translation of the words Qalb and Fuād which is only limited to the heart does not get a complete concept. Qalb and Fuad have the meaning of heart in Indonesian there is a very important difference and should not be ignored. The purpose of this study was to determine the relationship between the meanings of the words Qalb and Fuād in terms of the semantic field. This type of research is library research, because the data collection is based on the literature. The approach used in this study is a qualitative descriptive approach that is analytical. Research sources come from primary data and secondary data. Al-Qur'an study methods and interpretations were chosen according to the objectives and problems studied related to pre-existing substances. The data collection method used is document study, and learns from primary data sources and secondary data in the form of books, books, scientific articles and journals related to the theme of synonymy analysis of the terms qalb and fu'ad.The results showed that the meaning of the word Qalb or Qalbu in a physical sense can be interpreted as heart. While Fuad is the part of the heart that is related to makrifat. Fuād is the place of seeing and the part of the heart is knowledge. The relationship between the meanings of the words qalb and fu'ad in meaning through the semantic field, Qalb has the meaning of a soul dimension that has the ability to understand like 'aql. and also the word fu'ad which is taken from the word fā'idah (useful), because it can be seen that there are various kinds of love for Allah SWT, so that they get benefits from Him. Lafadz qalb and fu'ad have almost related meanings, qalb is focused on things that are immaterial and psychological, spiritual nature that is able to understand and determine the good and bad of a soul, As for fu'ad is called an honest heart (conscience). ) and is the potential of qalb, the place where a firm decision has been reached or something that has been bound, to be precise, fu'ad is a container of belief.